Reliability, validity, and injury predictive value of the Functional Movement Screen: A systematic review and meta-analysis - Bonazza, N. A.; Smuin, D.; Onks, C. A.; Silvis, M. L.; Dhawan, A. (The American Journal of Sports Medicine, 2017)
Background: The Functional Movement Screen (FMS) is utilized by professional and collegiate sports teams and the military for the prevention of musculoskeletal injuries. Hypothesis: The FMS demonstrates good interrater and intrarater reliability and validity and has predictive value for musculoskeletal injuries. Study Design: Systematic review and meta-analysis. Methods: A systematic review and meta-analysis were conducted using a computerized search of the electronic databases MEDLINE and ScienceDirect in adherence with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Extracted relevant data from each included study were recorded on a standardized form. The Cochran Q statistic was utilized to evaluate study heterogeneity. Pooled quantitative synthesis was performed to measure the intraclass correlation coefficient (ICC) for interrater and intrarater reliability, along with 95% CIs, and odds ratios with 95% CIs for the injury predictive value for a score of =14. Results: Eleven studies for reliability, 5 studies for validity, and 9 studies for the injury predictive value were identified that met inclusion and exclusion criteria; of these, 6 studies for reliability and 9 studies for the injury predictive value were pooled for quantitative synthesis. The ICC for intrarater reliability was 0.81 (95% CI, 0.69-0.92) and for interrater reliability was 0.81 (95% CI, 0.70-0.92). The odds of sustaining an injury were 2.74 times with an FMS score of =14 (95% CI, 1.70-4.43). Studies for validity demonstrated flaws in both internal and external validity of the FMS. Conclusion: The FMS has excellent interrater and intrarater reliability. Participants with composite scores of =14 had a significantly higher likelihood of an injury compared with those with higher scores, demonstrating the injury predictive value of the test. Significant concerns remain regarding the validity of the FMS.